Philosophy of mind historical and contemporary perspectives - Morton, Peter A. 1952-; Mylopoulos, Myrto (Broadview Press, 2020)
"This book introduces students to the principal issues in the philosophy of mind by tracing the history of the subject from Plato and Aristotle through to the present day. Over forty primary source readings are included. Extensive commentaries from the editors are provided to guide student readers through the arguments and jargon and to offer necessary historical context for the readings. This new edition examines some of the most exciting recent developments in the field, including advances in theories about the mind’s relation to action and agency."--
Keywords: Philosophy of Mind; Philosophy of mind / History / Textbooks; Mind and body / History / Textbooks; Mind and body; Philosophy of mind; History; Textbooks